Ecosystems and Their Services in Da Bac District, Hoa Binh Province - Hien, Nguyen Van; Mai, Nguyen Thi Ngoc; Phuong, Nghiem Thi; Mai, Doan Huong (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Da Bac - the largest district of Hoa Binh province, has an undeveloped economy and  more difficult living condition, in comparison with other districts, cities in the province. Therefore, it is necessary to analyze the ecosystem diversity and ecological services of ecosystems of Da Bac district for sustainable socio-economic development. In this study, different ecosystems of Da Bac have been identified based on the basic understandings of ecology. Then, the important levels/values of their ecosystem services were analyzed and estimated to suggest important ecosystems for protection priorities and help the policy makers allocate resources properly between competing usage demands for a sustainable development. Keywords: Ecosystem, ecological services, sustainable development.